Formation of the target professional Competences of CLIL Teachers - Gulnar Karipbayeva4, Gulnara Azhibekova5Tanat Ayapova1, Dana Shayakhmetova2, Ainagul Tautenbayeva3, (Opción, 2019)
This article is devoted to CLIL (Subject and Language Integrated Learning) – describes teaching methods, where subjects are taught in foreign languages via comparative qualitative research methods. As a result, assessment in CLIL remains one of the aspects that poses difficulties as it depends on the national or local policy and established practices to a great extent, and causes intense discussions even within the CLIL community itself. In conclusion, teachers still lack competences in preparing/designing teaching materials for the CLIL class, the skills only acquired through long practice.